2020
DOI: 10.1155/2020/5924856
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils of Lemongrass (Cymbopogon citratus Stapf) Induces Apoptosis and Cell Cycle Arrest in A549 Lung Cancer Cells

Abstract: Essential oils were extracted from the culm and leaf of Cymbopogon citratus collected from different regions of Vietnam and analyzed using GC/MS. The results showed that citral is the major component accounting for 61.20%–76.46% of the essential oils. The citral content was higher in the essential oil obtained from the leaf than in that from the culm of lemongrass in all regions. In particular, camphene, valerianol, and epi-α-muurolol can be used to differentiate essential oils originating from leaves versus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 20 publications
(21 reference statements)
2
38
0
Order By: Relevance
“…The EOCc at the evaluated doses produced a reduction in the total number of tumors, a decrease in the frequency of tumors per group (44% less with the dose of 200 mg/kg/day), as well as in the average tumor volume and the cumulative tumor volume ( Table 2 , Figure 3 ); also, at the histological level, a decrease in the percentage of necrosis and mitosis was observed ( Figure 5 C–E). An in vitro study showed cytotoxicity of the EOCc on MCF-7 breast cancer cells [ 22 , 39 ]. It was also effective on LNCaP and PC-3 prostate cell lines, and on SF-767 glioblastoma cell lines, showing that the activity of the EOCc was statistically equal to its main component, citral [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EOCc at the evaluated doses produced a reduction in the total number of tumors, a decrease in the frequency of tumors per group (44% less with the dose of 200 mg/kg/day), as well as in the average tumor volume and the cumulative tumor volume ( Table 2 , Figure 3 ); also, at the histological level, a decrease in the percentage of necrosis and mitosis was observed ( Figure 5 C–E). An in vitro study showed cytotoxicity of the EOCc on MCF-7 breast cancer cells [ 22 , 39 ]. It was also effective on LNCaP and PC-3 prostate cell lines, and on SF-767 glioblastoma cell lines, showing that the activity of the EOCc was statistically equal to its main component, citral [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that the anti-tumor effect of the EOCc observed in our study could be due to the high content of citral in the sample. A study reported with EOCc and citral produced a decreased expression of Bcl-xL and Mcl-1 antiapoptotic factors, in turn, suppressed the proliferation/survival of small lung cancer cells (SCLC cells), [ 23 , 39 ] also decreased cell proliferation, increasing intracellular (reactive oxygen species) ROS, altering the potential of mitochondrial membrane, and initiating apoptosis in cervical cancer cell lines HeLa and ME-180 [ 40 ]. However, we did not test additional assays on breast cancer cell line to stablish any relationship between the antioxidant activity and breast cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, also known as programmed cell death, is a specific cell death pathway characterized by morphological changes, such as chromatin condensation, nuclear fragmentation, and the formation of apoptotic bodies [ 41 ]. The cell cycle is also associated with apoptosis; cell cycle arrest in the sub-G1 phase leads induces apoptosis via effects on various signaling molecules and regulatory factors [ 42 ]. In this study, we therefore investigated the effects of TLE on cell cycle arrest in the sub-G1 phase and the population of apoptotic bodies in H 2 O 2 -treated Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…In female Balb/c mice, essential oil administration showed a protective effect against N-methyl-N-nitrosurea-induced mammary carcinogenesis by inducing DNA damage in peripheral leucocytes [ 266 ]. In A549 lung cancer cells, essential oil of lemongrass induced cell cycle arrest and apoptosis by upregulating the expression of Bax [ 267 ].…”
Section: Herbal Teas and Autophagymentioning
confidence: 99%